Predominance of Severe Plasma Leakage in Pediatric Patients With Severe Dengue in Puerto Rico. (1st May 2022) - Paz-Bailey, Gabriela; Sánchez-González, Liliana; Torres-Velasquez, Brenda; Jones, Emma S; Perez-Padilla, Janice; Sharp, Tyler M; Lorenzi, Olga; Delorey, Mark; Munoz-Jordan, Jorge L; Tomashek, Kay M; Waterman, Stephen H; Alvarado, Luisa I; et al.
Abstract: Background: We evaluated clinical and laboratory findings among patients with nonsevere or severe dengue in Puerto Rico to examine whether clinical manifestations vary by age. Methods: During 2012–2014, we enrolled patients who arrived at the emergency department with fever or history of fever within 7 days of presentation. Serum samples were tested for dengue virus (DENV) by reverse transcriptase-polymerase chain reaction (RT-PCR) and IgM enzyme-linked immunosorbent assay (ELISA). Severe dengue was defined as severe plasma leakage or shock, severe bleeding, or organ involvement at presentation, during hospitalization, or follow-up. Results: Of 1089 dengue patients identified, 281 (26%) were severe. Compared to those with nonsevere dengue, patients with severe dengue were more often aged 10–19 years (55% vs 40%, P < .001) and hospitalized (87% vs 30%, P < .001). Severe plasma leakage or shock was more common among children aged 0–9 (59%) or 10–19 years (86%) than adults (49%) ( P < .01). Severe bleeding was less common among 10–19 year olds (24%) compared to 0–9 year olds (45%) and adults (52%; P < .01). Conclusions: Severe plasma leakage was the most common presentation among children, highlighting important differences from adults. Vaccination against dengue could help prevent severe dengue among children in Puerto Rico. Abstract : We evaluated patients with dengue in Puerto Rico. Most cases were among children. Severe plasma leakage was the most common presentation among children, highlighting important differences from adults. Vaccination could help prevent severe dengue among children in Puerto Rico.